Black Hiram: Freemasonry in the Eyes of the Nation of Islam (1930–1995) - Duranton, Nils Harley (Journal of Africana religions, 2025)
This article analyzes the relationship between the Nation of Islam and American Freemasonry throughout the various stages of the Nation’s history. As a Black nationalist organization, the Nation of Islam has maintained a complex dialogue with the Masonic milieu: while considering this sociability to emanate from white American culture, the Nation of Islam’s theologians have claimed that high-degree Masons would be fully aware of the veracity of the Muslim religion. What is more, its preachers have sometimes made use of typically Masonic symbols or themes, believing these elements to herald the rebirth of the African American community in the twentieth century. These considerations lead us to conclude that the Nation of Islam claims to fulfill the promises that Freemasonry supposedly could not keep, thus maintaining the belief that the Masonic brotherhood was akin to a dangerous deception seeking to betray the trust of Black Americans.